Hemangioblastoma of the spinal nerve root - (:unkn) unknown (My University, 2003)
Spinal root haemangioblastomas are very rare tumors. A 70-year-old male patient admitted to our clinic with low back and both legs pain of one year's duration. Magnetic resonance imaging revealed a solid mass lesion at T-12 level. The contrast enhancing mass was intradural in location. T-12 laminectomy was performed and a highly vascular mass originated at the T-12 nerve root was totally removed. Histopathological examination revealed diagnosis of haemangioblastoma. He was then screened for von Hippel Lindau disease. No stigmata of this disease were found. The postoperative period was uneventful. He was discharged with no complaints. Spinal root haemangioblastoma should be kept in mind in a patient with highly enhancing spinal intradural mass.
Keywords: Hemangioblastoma; Spinal nerve root; Von Hippel Lindau disease